2022
DOI: 10.1021/acs.jproteome.2c00375
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma Metabolites and Lipoproteins with Rh and ABO Blood Systems in Healthy Subjects

Abstract: This study investigated the associations between the levels of 27 plasma metabolites, 114 lipoprotein parameters, determined using nuclear magnetic resonance spectroscopy, and the ABO blood groups and the Rhesus (Rh) blood system in a cohort of n = 840 Italian healthy blood donors of both sexes. We observed good multivariate discrimination between the metabolomic and lipoproteomic profiles of subjects with positive and negative Rh. In contrast, we did not observe significant discrimination for the ABO blood gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Therefore, our results and previous studies suggest a link of ABO gene polymorphisms with protection against ACS that may be partially related with HDL-C. The association of ABO groups with HDL plasma levels has been previously reported [ 35–37 ] presupposing a modification of lipoprotein metabolism but the mechanisms involved are still unknown [ 35 ]. Additional studies, such as GWAS, exome sequencing studies, and recently “exome chip” in a larger number of individuals should be undertaken.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, our results and previous studies suggest a link of ABO gene polymorphisms with protection against ACS that may be partially related with HDL-C. The association of ABO groups with HDL plasma levels has been previously reported [ 35–37 ] presupposing a modification of lipoprotein metabolism but the mechanisms involved are still unknown [ 35 ]. Additional studies, such as GWAS, exome sequencing studies, and recently “exome chip” in a larger number of individuals should be undertaken.…”
Section: Discussionsupporting
confidence: 74%
“…The mechanism for the association of RhD− individuals with subclinical atherosclerosis might be related to the fact that lipoproteins have been shown to differ between RhD groups but not between ABO groups [ 13 ]. However, one study reported a better lipid profile in RhD− compared to RhD+ individuals [ 14 ], which contradicts our results.…”
Section: Discussionmentioning
confidence: 99%
“…The ABO blood group system has previously been associated with several circulatory diseases [ 5 , 6 , 7 ], and it is stated that non-O blood group individuals are associated with increased incidence of arterial thromboembolic events [ 8 , 9 , 10 ], such as myocardial infarction (MI), but there are more conflicting results as to whether other forms of CVD are associated [ 10 , 11 , 12 ]. Few studies are available on the RhD blood group and its role in the pathogenesis of circulatory disease, but some have suggested that there are associations between RhD and dyslipidemia, which is a risk factor for CVD [ 13 , 14 ]. Studies assessing the roles of ABO and RhD in subclinical atherosclerosis as potential risk markers are sparse, and the studies available have primarily included individuals already considered high-risk.…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy, sensitivity, specificity, the area under the ROC curve (AUROC), and corresponding 95% CIs were calculated according to the standard definitions and given as average over the 100 re-samplings. The significance of the models was determined with a permutation-test using n = 1000 permutations [ 34 ].…”
Section: Methodsmentioning
confidence: 99%